Efficacy and Safety of a Novel Tapered-Tip Sheath System for Biliary-Lesion Tissue Sampling: A Randomized Controlled Trial - Hirokazu Okada; Norimitsu Uza; Tomoaki Matsumori; Hajime Yamazaki; Muneji Yasuda; Takeshi Kuwada; Yoshihiro Nishikawa; Takahisa Maruno; Masahiro Shiokawa; Atsushi Takai; Ken Takahashi; Akihisa Fukuda; et al. (Gut and Liver)
Background/Aims: Pathological evaluation is crucial for diagnosing biliary lesions and determining appropriate treatment strategies. However, tissue sampling via the transpapillary route can be difficult. In this study, we aimed to assess the efficacy and safety of a novel tapered-tip sheath system for tissue sampling from biliary strictures. Methods: This single-center, randomized, parallel-group clinical trial included patients aged 20 to 85 years admitted to Kyoto University Hospital for biliary strictures. The patients were randomly assigned (1:1) to a new or conventional method group. The primary outcome was technical success of biopsy at the target bile duct using the assigned method, as determined in accordance with the intention-to-treat principle. Adverse events were assessed in all eligible patients. Results: Fifty-six patients were assessed for eligibility between September 2020 and March 2023; 50 patients were enrolled. The patients were randomly divided into the new (n=25) method group and the conventional (n=25) method group. Technical success was achieved in 96.0% (24/25) and 48.0% (12/25) of patients in the new and conventional method groups, respectively (risk ratio, 2.00; 95% confidence interval [CI], 1.32 to 3.03; risk difference, 48.0%; 95% CI, 27.0% to 69.0%; p<0.001). Adverse events occurred in 4.0% (1/25) and 36.0% (9/25) of patients in the new and conventional method groups, respectively (risk ratio, 0.11; 95% CI, 0.02 to 0.81; risk difference, -32.0%; 95% CI, -52.3% to -11.7%; p=0.005). Conclusions: The novel tapered-tip sheath system is a promising option for precisely and safely delivering biopsy forceps to target sites, thereby facilitating the diagnosis of biliary strictures.